2020
DOI: 10.1021/acsomega.9b04444
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lithium Compound Addition on the Dehydration and Hydration of Calcium Hydroxide as a Chemical Heat Storage Material

Abstract: Many studies on calcium hydroxide [Ca­(OH)2] as a chemical heat storage material have been conducted. Generally, calcium hydroxide undergoes a dehydration reaction (heat storage operation) efficiently at about 400 °C or higher. In this study, we aimed to lower the dehydration reaction temperature and increase the dehydration reaction rate to expand the applicability of calcium hydroxide as a chemical heat storage material. For the purpose of improving the dehydration reactivity, calcium hydroxide with added li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Salt hydrates such as MgCl 2 $6H 2 O, 14,15 LiOH$H 2 O, 16 and metal sulfates 15,[17][18][19] have been used as CHS materials in the temperature range of 100-250 C. Mg(OH) 2 , [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Ca(OH) 2 , 28,[35][36][37] and MgCO 3 (ref. 38) can be used to store energy in the temperature range of 200-500 C. These materials exhibit high energy density and the property of reversibility.…”
Section: Introductionmentioning
confidence: 99%
“…Salt hydrates such as MgCl 2 $6H 2 O, 14,15 LiOH$H 2 O, 16 and metal sulfates 15,[17][18][19] have been used as CHS materials in the temperature range of 100-250 C. Mg(OH) 2 , [20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Ca(OH) 2 , 28,[35][36][37] and MgCO 3 (ref. 38) can be used to store energy in the temperature range of 200-500 C. These materials exhibit high energy density and the property of reversibility.…”
Section: Introductionmentioning
confidence: 99%
“…The heat affected zone (HAZ) is a zone of the base material that was not melted but impacted by the heat generated during the laser scabbling process. According to Maruyama et al [22], the temperature for the dehydration reaction of Ca(OH) 2 is 400 • C or higher. From this study it was reported that microcracks occurred in cement-based materials due to the breaking of chemical and physical bonds caused by temperature.…”
Section: Morphological Analysismentioning
confidence: 99%
“…From this study it was reported that microcracks occurred in cement-based materials due to the breaking of chemical and physical bonds caused by temperature. The dehydration of calcium hydroxide is shown in Equation (3) [22]:…”
Section: Morphological Analysismentioning
confidence: 99%
“…The lithium salts used as dopants are listed in Table 2. As can be seen in the table, the main doping lithium-based salts are LiCl [63,64], LiOH [61,64], LiNO3 [65,66], Li4SiO4 [67] and LiKNO3 [62,68]. These salts have been used in multiple investigations, showing good thermal stability and expanding the applicability of the compounds as a heat storage materials.…”
Section: Lithium In Tcs Chemical Reactionsmentioning
confidence: 99%